2021
DOI: 10.1080/21655979.2021.1962686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluid shear stress on expression of focal adhesion kinase in MG-63 human osteoblast-like cells on different surface modification of titanium

Abstract: This study aimed to investigate the effect of fluid shear stress (FSS) on cell proliferation and expression of focal adhesion kinase (FAK) in MG-63 cells on different modified titanium surfaces. MG63 cells were cultured on three different surfaces: glass slide, polished treatment (PT) titanium surface and sandblasted/acid-etched surfaces (SLA) titanium surface. The surface topography and roughness were evaluated by scanning electron microscopy (SEM) and atomic force microscopy (AFM), respectively. The cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In this regard, active bone cells-including both osteoblasts and osteoclasts, as well as their respective precursors-have been shown to activate distinct mechanical transduction pathways that are known to modulate cellular behavior, including proliferation, differentiation, and functional activity, in response to distinct forms of mechanical stress of the local microenvironment, in which both compressive and tensile stresses are included [65]. Of additional relevance, the induction of fluid shear stress-by the flow of tissue fluid at the lacunar-canalicular bone system [66]-has recently been found to modulate the mechanical transduction of the osteoblastic behavior at the bone-to-implant interface, via the enhancement of the cell proliferation and differentiation [67], potentially contributing to the attained outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, active bone cells-including both osteoblasts and osteoclasts, as well as their respective precursors-have been shown to activate distinct mechanical transduction pathways that are known to modulate cellular behavior, including proliferation, differentiation, and functional activity, in response to distinct forms of mechanical stress of the local microenvironment, in which both compressive and tensile stresses are included [65]. Of additional relevance, the induction of fluid shear stress-by the flow of tissue fluid at the lacunar-canalicular bone system [66]-has recently been found to modulate the mechanical transduction of the osteoblastic behavior at the bone-to-implant interface, via the enhancement of the cell proliferation and differentiation [67], potentially contributing to the attained outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical stimulation is an important regulatory factor for bone growth, reconstruction, and metabolism. Number experimental studies have investigated osteogenic effects under mechanical stress ( Chermside-Scabbo et al, 2020 ; Eichholz et al, 2020 ; Jeon et al, 2021 ; Lei et al, 2021 ). The influence of different mechanical forces on bone tissue produces various effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the in-depth study of bone ingrowth between internal fixation materials and bone interface has encouraged the study of material-bone interface-mechanical stimulation as an emerging focus. Lei et al(2021) reported the effect of FSS on human MG-63 osteoblast-like cells on titanium with different surface modifications, which was particularly evident on the implant-bone interface. This study found that FSS (12 dyn/cm 2 ) significantly induced cell proliferation and upregulated the expression level of focal adhesion kinase (FAK), which the authors speculated that FAK may play a key role in the mechanical transduction of the implant-bone interface ( Lei et al, 2021 ).…”
Section: Mechanical Stimulation With Osteoblastsmentioning
confidence: 99%
“…Staining working liquid was added and incubated at room temperature in the dark for 30 min. Cells with alkaline phosphatase activity were dyed purple-black or blue-black [ 22 ].…”
Section: Methodsmentioning
confidence: 99%